Situation Report: Poland, 19 March 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. On the Eve of the Party Conference Church and State on Collision Course over Ban on Crosses in Schools / by Ewa Celt Prominent Writer Arrested United Peasant Party Prepares for Its Congress / by Ewa Celt The Zloty Devalued Delays in Sentencing Sundry Items